Pseudomyxoma peritonei with endometrial mucinous carcinoma and appendicular mucinous tumor: An unusual association. Issue 1 (March 2016) - Emam, Eman; Ghanim, Ahmad; Ghanim, Ayman
Abstract: The association between pseudomyxoma peritonei and appendicular or ovarian mucinous tumors is usually reported in the literature, while the association with endometrial carcinoma is exceptional. Although there has been always a continuous debate regarding its primary origin, tumors of the appendix and ovary remain the most common primary sites for this disease. The association of pseudomyxoma peritonei with two primaries from endometrial mucinous adenocarcinoma and appendicular mucinous tumor is very rare. So, we report this case to raise awareness among clinicians about this rare tumor association.